Baptism in the early church - Stander, Hendrick F.; Louw, Johannes P. (Leeds, England : Carey Press, Reformation Today Trust ; Webster, N.Y. : Evangelical Press USA, 2004)
This book demonstrates that believer's baptism did not simply disappear after the apostolic era, but continued to be the accepted practice for centuries. Infant baptism became part of ecclesiastical practice gradually, apart from apostolic injunction. For this reason it must be called into question and rejected as a suitable practice for Christian churches.
First published in 1988 and 1994 (revised ed.) by Didaskalia Publishers, South Africa.
nbl-06 rel.
"A Carey Press title published by Reformation Today Trust in cooperation with the Association of Reformed Baptist Churches of America" - t.p. verso.
Includes bibliographical references.
Keywords: Baptism -- History of doctrines -- Early church, ca. 30-600.